Due-Date assignment with acceptable lead-times on parallel machines - Mor, Baruch; Mosheiov, Gur (Computers & operations research, 2024)
•We study scheduling and due-date assignment problems with acceptable lead times.•The machines settings are: parallel identical, uniform and unrelated machines.•A common lead-time is assumed in the first set of problems.•Then, job-dependent lead-times and identical earliness and tardiness costs are assumed.•Pseudo-polynomial dynamic programming algorithms are introduced for all problems. The paper studies scheduling and due-date assignment problems on parallel machines. We consider the DIF (different due date) model, which assumes job-dependent acceptable lead-times. Thus, in addition to the classical job-earliness and job-tardiness costs, the scheduler is penalized if an assigned due-date exceeds its lead-time. First, the case of a common lead-time is studied. Then we focus on the setting of job-dependent lead-times and identical (earliness, tardiness, and lead-time) costs. Both models are examined for parallel identical, uniform, and unrelated machines. The case in which the option of job-rejection is allowed is also considered. For all these NP-hard problems, efficient pseudo-polynomial dynamic programming algorithms are introduced and tested. Our numerical tests indicate that problems containing 500 jobs are solved in less than 0.3 s.